2016
DOI: 10.1108/meq-04-2015-0057
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of diatomite from Sig region (West Algeria) for industrial application

Abstract: Purpose-Diatomite also known Kieselguhr, is a non-metallic mineral composed of the skeletal remains of microscopic single-celled aquatic algae called diatoms. The purpose of this paper is to test and to evaluate the diatomite of Sig region (West Algeria) to substitute the main mould powder used in continuous casting of steel for thermal insulation and lubrication. Design/methodology/approach-To assess the behavior of diatomite at different temperatures, a combination of simultaneous scanning calorimetric and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The calcination is part of the sample pretreatment and is crucial for thermal stability. It reduces the mass of biosilica by about 40%, which is in accordance with other studies reporting a mass loss of 20% (Meradi et al, 2016) to 50% (Jiang et al, 2014) for the calcination of cultivated and chemically pretreated diatom cells. For untreated diatomite, lower losses of about 10% are reported (Fuya et al, 1995;Nowak et al, 2019).…”
Section: Thermal Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…The calcination is part of the sample pretreatment and is crucial for thermal stability. It reduces the mass of biosilica by about 40%, which is in accordance with other studies reporting a mass loss of 20% (Meradi et al, 2016) to 50% (Jiang et al, 2014) for the calcination of cultivated and chemically pretreated diatom cells. For untreated diatomite, lower losses of about 10% are reported (Fuya et al, 1995;Nowak et al, 2019).…”
Section: Thermal Analysissupporting
confidence: 92%
“…No significant water signals due to pore water removal or condensation of the surficial silanol groups to siloxanes (Meradi et al, 2016) can be observed in both DTA/TG and MS graphs. To a certain degree, siloxane groups could have already formed during the thermal pretreatment of the biosilica at 550°C.…”
Section: Thermal Analysismentioning
confidence: 94%
“…Similar observations on the morphology of Algerian Sig diatomite have been reported by several authors. 3,5,21,22 In addition, there is a significant influence of washing on the acid-base behaviour of diatomaceous earth powders. In fact, washing leads to an overall and significant increase in the values of ΔG AB .…”
Section: Characterization Of the Different Chromatographic Supportsmentioning
confidence: 99%
“…In order to overcome these problems and to increase the applicability temperature of diatomite as well, calcium oxide was added, in the form of chalk, with different mass ratios from 0 to 30%. This reaction between chalk and the diatomitic silica will result in the formation of wollastonite (CaO.SiO 2 ) mineral and accordingly, the chance of cristobalite formation will be decreased, resulting in increasing the applicable firing temperature (Kashcheev et al 2009a;Meradi et al 2015;Merado et al 2016;Galzerano et al 2018).…”
Section: Introductionmentioning
confidence: 99%